Ransomware: stages, detection and evasion - Yus Kamalrul, Mohamed Yunus; Syahrulanuar, Ngah (IEEE, 2022)
Ransomware attacks has been increasing lately with companies suffer monetarily, wasted business opportunity and wasted time. Big companies are now targeted as they are more profitable for ransomware threat actor. This paper discuses on stages of ransomware attacks starting from reconnaissance to extortion. It also discusses on steps that organization should take to prevent ransomware attack and several detection methods for ransomware. Other than that, it lists anti-analysis and evasion method used by ransomware to evade detections. Lastly, it discusses the latest ransomware attacks.